Analisis Pengaruh Profitabilitas, Financial Leverage Dan Dividen Payout Ratio Terhadap Income Smoothing Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2014 – 2018 - Muhamad Khoirul Kabib; Hardiwonoto Hardiwinoto; Ida Kristiana (MAKSIMUM, 2020)
This study was structured to determine the significance level of the Profitability, Financial Leverage and Dividend Payout Ratio variables against Income Smoothing in Manufacturing Companies listed on the IDX for the 2014-2018 period. This study used a purposive sampling technique. The sample used in this study were 49 companies listed on the Indonesia Stock Exchange (BEI). Data obtained from the company's financial statements for 2014-2018. The analysis used in this study is multiple regression analysis to determine the effect of Profitability, Financial Leverage and Dividend Payout Ratio on Income Smoothing at Manufacturing Companies listed on the IDX for the 2014-2018 period. Based on the classic assumption test, namely normality test, heteroscedasticity test, multicollinearity test, and the autocorrelation test found no deviation. This shows that the available data has met the requirements for use in multiple linear regression equation models. The results of the partial analysis show that the Profitability and Financial Leverage variables have a significant positive effect on Income Smoothing. Meanwhile, the Dividend Payout Ratio variable has a negative and insignificant effect on income smoothing. Meanwhile, the simultaneous test results show that the three variables have a significant positive effect on income smoothing. The predictive ability of the three variables on Income Smoothing was 32.8%, while the other 67.2% were explained by other variables outside the independent variables in the study.